Case Report: Allogeneic Stem Cell Transplantation Following Induction With CPX-351 in Patients With Acute Myeloid Leukemia Is Feasible - Vucinic, Vladan; Jentzsch, Madlen; Schwind, Sebastian; Bach, Enrica; Leiblein, Sabine; Remane, Yvonne; Rieprecht, Susanne; Otto, Sandra; Kubasch, Anne-Sophie; Behre, Gerhard; Cross, Michael; Platzbecker, Uwe; et al. (Frontiers in Oncology, 2020)
Acute myeloid leukemia with myelodysplasia-related changes (AML-MRC) and treatment-related acute myeloid leukemia (tAML) after chemotherapy or radiation therapy for other neoplasms are associated with poor outcomes. CPX-351, a dual-drug liposomal encapsulation of daunorubicin and cytarabine, has been shown to improve outcomes in AML-MRC and tAML compared with standard 7+3 regimens. Here we report the cases of 4 consecutive patients with AML-MRC or tAML who received CPX-351 as outpatient induction therapy immediately followed by allogeneic hematopoietic stem cell transplantation (allo-HSCT). Two patients received allo-HSCT in remission (1 in complete remission and 1 in partial remission) and 2 patients received allo-HSCT in aplasia (1 at 11 days and 1 at 52 days after the start of induction therapy with CPX-351). With a median follow-up of 188 days after allo-HSCT, all but 1 patient are alive and 2 are in remission. Further studies will help define and expand the role of CPX-351 in the treatment of AML-MRC and tAML, especially in patients expected to undergo allo-HSCT.